MULTIMEDIA INTERAKTIF BERMUATAN KEANEKARAGAMAN BUDAYA INDONESIA PADA PEMBELAJARAN TEMATIK UNTUK MENINGKATKAN RASA CINTA TANAH AIR SISWA SEKOLAH DASAR - Mahilda Dea Komalasari, Ahmad Mabruri Wihaskoro (Universitas PGRI Yogyakarta, 2018)
This study aims to develop interactive multimedia-charged cultural diversity of Indonesia on thematic learning to improve the nasionalism student's sense of love. This research type isresearch development with subject of elementary school student at Winongo Elementary School.The research method used is research development. Data collection in this study includeobservation, questionnaires, interviews and tests. Method of data analysis conducted in thisresearch is quantitative analysis using paired sample t-test. The results of this study indicate thatinteractive multimedia development results from the content feasibility aspects, presentation,language, and kegrafikan, according to the expert as a whole is categorized as feasible. Basedon the assessment of material experts, interactive multimedia categorized 'good' with the value of80 and based on the assessment of media experts, interactive muktuedia berkategori 'very good'with a score of 87.5. Thematic learning by using interactive multimedia result of effectivedevelopment improves the love of nasionalism students of grade IIIA SDN Winongo. Thisresearch has both theoretical and practical benefits. The theoretical benefits are: 1) thisresearch can enrich the theoretical study on improving the character of love of the nasionalismof students through the development of interactive multimedia containing the diversity ofIndonesian culture; 2) this research can provide theoretical contribution about the utilization ofinformation and communication technology especially in the form of interactive multimedia; and3) this research can find best practice in instilling nasionalism love value. As for the practicalbenefits: 1) this research can improve the character of the nasionalism student love, as well asfacilitate the students to understand and practice the character of love nasionalism; 2) thisresearch can give positive contribution to teachers, lecturers, and education practitioners inorder to improve the character of learners by utilizing technology; and 3) this research canprovide a deeper insight and insight into the use of technology to improve the character ofstudents, one of them interactive multimedia technology.Keywords:interactive multimedia, Indonesiaâ€™s culture diversity, nasionalismÂ